Development of STEP AP224 Extractor for Interfacing Feature Based CAPP to STEP-NC (AP238) - Srivastava, Deepanshu; Komma, Venkateswara Rao (Machine intelligence research (Print), 2019)
Manufacturing features represent area of interest on the machinable surface of a part, which can provide a unique set of removable volumes from part. Feature description in standard for exchange of product (STEP) AP224 is an efficient neutral format for the development of feature based process planning. Process planning information of features can be converted to numerical control (NC) code to have complete manufacturing information of part. STEP-NC code provides an efficient manufacturing information model compared to G-M codes. In this work, an interface is developed for extraction of feature information available in AP224 (AIM) format and the ruled-based approach is used to select different process planning parameters. A graphical user interface (GUI) is developed for the interface for displaying features information as represented in AP224 file. Furthermore, the interface generates STEP-NC code in AP238 format. The developed interface has three modules. 1) Module I: Reading interface for STEP AP224 file and development of GUI. 2) Module II: Selection of feature based process planning parameters. 3) Module III: Writing interface for STEP-NC (AP238). The developed interface has been implemented in Java through Java standard data access interface (JSDAI™). The generated STEP-NC AP238 code for the test part has been successfully simulated on STEP-NC Machine™, an AP238 simulator. This article also provides an in-depth view of application interpreted model (AIM) representation format of STEP for AP224 and AP238.